2003
DOI: 10.1177/00343552030460030301
|View full text |Cite
|
Sign up to set email alerts
|

Work Barriers Experienced and Job Accommodations Used by Persons with Arthritis and Other Rheumatic Diseases

Abstract: Many people with arthritis become work disabled, but little is known about (a) the types of work barriers they experience and (b) their use of job accommodations. Our objectives were to describe work barriers and use of accommodations and to examine factors associated with accommodation use in persons with arthritis at risk for work disability. Barrier assessment was conducted using the Work Experience Survey. Factors associated with accommodation use were analyzed by logistic regression. The overwhelming majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 15 publications
3
43
0
1
Order By: Relevance
“…These results on the use of job accommodations by people with lupus are comparable to the findings of some, but not all, previous studies on patients with musculoskeletal conditions, including lupus (23,27,36). Most notably, in 1 study of individuals with musculoskeletal conditions, only 18% of respondents reported that they used job accommodations (23).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…These results on the use of job accommodations by people with lupus are comparable to the findings of some, but not all, previous studies on patients with musculoskeletal conditions, including lupus (23,27,36). Most notably, in 1 study of individuals with musculoskeletal conditions, only 18% of respondents reported that they used job accommodations (23).…”
Section: Discussionsupporting
confidence: 86%
“…The relationship between workplace activity limitations and job accommodations has been described in studies of individuals with osteoarthritis and inflammatory arthritis (36). Other studies using more general measures of functional limitations (e.g., the Health Assessment Questionnaire) also have found that greater functional limitations in patients with rheumatic diseases are associated with greater use of job accommodations (27). Education level also was significantly associated with the use of job accommodations.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations